A Toroidal Metamaterial Switch. Issue 4 (6th December 2017) - Gupta, Manoj; Srivastava, Yogesh Kumar; Singh, Ranjan
Abstract: Toroidal dipole is a localized electromagnetic excitation that plays an important role in determining the fundamental properties of matter due to its unique potential to excite nearly nonradiating charge–current configuration. Toroidal dipoles are recently discovered in metamaterial systems where it is shown that these dipoles manifest as poloidal currents on the surface of a torus and are distinctly different from the traditional electric and magnetic dipoles. Here, an active toroidal metamaterial switch is demonstrated in which the toroidal dipole can be dynamically switched to the fundamental electric dipole or magnetic dipole, through selective inclusion of active elements in a hybrid metamolecule design. Active switching of nonradiating toroidal configuration into highly radiating electric and magnetic dipoles can have significant impact in controlling the electromagnetic excitations in free space and matter that can have potential applications in designing efficient lasers, sensors, filters, and modulators. Abstract : Toroidal dipole excitation can be dynamically switched to the fundamental electric dipole or magnetic dipole, through selective inclusion of the active elements in a mirrored configuration of Fano resonators. Optical switching between various multipole excitations that range from nonradiating to strongly radiating configuration presents an innovative approach to implement more than one electromagnetic feature in a single device.